The Brazilian Constitution of 1988 and its ancient ghosts: comparison, history and the ever-present need to fight authoritarianism - Acunha, Fernando José Gonçalves; Arafa, Mohamed A.; Benvindo, Juliano Zaiden (Revista de Investigações Constitucionais, 2018)
Brazil is facing one of its most severe political crises since 2016, with several impacts in its gradual process of democratization. In this context, the main argument in this work is that many of the ghosts that scary the Brazilian society in the Twenty-First century are direct heirs of an unresolved (pre-constitutional) past, whose risks can be strongly perceived and whose solution is an urgent task. Every time there is political turmoil and a disturbance to the rule of law in the country, the support for democracy seems to dwindle. In this vein, this article aims to explore such contradictions and difficulties and how they still represent a threat to the Brazilian democracy through an analysis dedicated to the complex and ambiguous relation that the Constitution (and various of the Brazilian institutions, like the Supreme Court) has (have) established with the military dictatorship that lasted from 1964 until 1985. The authoritarian ghosts that up until now haunts the Brazilian reality, though inevitable due to the compromises that underpin it and the practices that stubbornly replicate the past into the very present, have at least to be disclosed and, as such, challenged by a learning process that only a militant memory is capable of making us aware of.